(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
القناع ـ mask ـ في أبسط معانيه وسيلة يتعامل الشاعر بوساطتها مع التراث، فيستدعي شخصيات تراثية متنوعة, وقد درس البحث استخدام المقالح لأقنعته في "ديوان عبد العزيز المقالح" فقط، ليكون ذلك نموذجاً لأشعاره جميعها التي استخدم فيها القناع. لقد تنوعت أقنعة الشاعر بين التراثية ـ غالباً ـ , والمعاصرة ـ نادراً ـ , وغلب عليها الشخصيات التراثية اليمنية, مثل قناع "وضاح اليمن" ، أما من حيث المضمون الذي حملته شخصيات القناع, فقد برز الموضوع السياسي اليمني أيضاً. وتناول البحث البنيات الفنية ـ الصورة، والموسيقا, واللغة ـ تناولاً أظهر فيه استخدام الشاعر لها, وجمالياتها, وقد انطلق منهاج الدراسة من النص قراءة وتحليلاً بغية الوصول إلى أغراضه, وجمالياته, وقد اقتضى الأمر أحياناً المقارنة مع عدد من الشعراء الذين استخدموا القناع. وأظهر البحث غلبة الموضوع الوطني على غيره من الموضوعات, وهذا يؤدي إلى أن الموضوع الوطني اليمني يسيطر على فكر الشاعر، وبيّن أن عالم المقالح الشعري يسهل دخوله بأدوات بحثيّة غير معقدة أيضا ، إذ تتكشف أبعاد النص من القراءة الأولى ، ودون أن يحتاج إلى إجهاد فكره باحثا عن أغراضه ، ودون تبني منهج نقدي ما ، الذي يتطلب أدوات تلازمه ، إنه السهل الممتنع . In its simplest terms, the mask is considered a means by which the poet deals with tradition. The means of the mask enables the poet to implement various traditional characters. This research studies the poet’s usage of the mask in Abed AL-Aziz’ collection only, and this is a model for all his poems in which he used the mask. The poet’s masks vary between what is mostly traditional and what is rarely modern and the traditional, dominated by traditional Yemeni characters like Waddah Al-Yaman. As for the content embodied by the mask characters, the Yemeni political topic also comes into play. This research deals with artistic structures, such as image, music, and language, focusing on the way in which the poet uses the above-mentioned concepts and how he explains and shows their beauty. The methodology adopted in this research relies on reading and analyzing the text in order to explain its purposes and beauty. Sometimes this research includes a comparative study of several poets who used the mask. This study sheds light on the dominance of traditional Yemeni characters in addition to the domination of the national Yemeni theme, leading to the conclusion that the traditional theme controls the poet’s thoughts, showing that Al Makaleh’s world of poetry is easy to deal with using simple methodological means.